Gender equality and women’s empowerment in rural transformation: From evidence to public action - Slavchevska, Vanya; Ndiaye, Tacko; Acosta, Mariola; Furst, Maurizio; Park, Clara; Rizk, Omnia; Sisto, Ilaria; Mane, Erdgin (Food and Agriculture Organization of the United Nations, 2023)
The slow, limited, and uneven progress on women’s empowerment and gender equality over the last decade clearly shows that rural transformation, with its focus on efficiency and productivity, is leaving women behind in addition to having negative impacts on the environment and nutrition. New inclusive models of rural transformation are called for. The study argues that treating gender equality and women’s empowerment as key in the process of rural transformation will lead to a more inclusive and resilient transformation of rural spaces. Women’s empowerment and gender equality are critical for the welfare of all women and girls, as well as instrumental for the achievement of other objectives, including increased household incomes and food security, dietary diversity, and resilience. To inform such models, this study critically assesses how rural transformation along with strategies to address climate change and nutrition, influence changes in women’s livelihoods and empowerment. It identifies key levers for enabling a transformation process that is resilient and truly inclusive: one that accelerates empowerment, guarantees women’s full and equal rights, and enables a gender-equal access to better livelihoods, food security and nutrition. Empowerment cannot be achieved through economic development alone; it requires transforming the laws, policies and practices that constrain women’s agency and achievements as well as dedicated investments to bridge the gaps between policies and outcomes on the ground. However, a detailed analysis shows that agricultural policies and investment plans do not adequately integrate gender equality considerations. The implications for inclusive rural transformation are discussed.